Design Patterns for Cyber-Physical Systems: The Case of a Robotic Greenhouse - Garro, Ricardo; Ordinez, Leo; Alimenti, Omar (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2011: Anais do I Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2011)
Cyber-physical systems (CPS) are a new discipline of research that involves electrical engineering, electronics, computer science, control and communications interacting with physical processes. This leads to a co-managed domain where both worlds (cyber and physical) must be taken into account to decide the actions to take. In this sense, this paper presents the design of a robotic greenhouse, which involves basically the greenhouse and a mobile robot interacting with the physical environment (collecting data and acting on plants). Thus, the main contribution is related to taking practical experience and generalize it by applying well-proven techniques to the development of CPS.